Adult Orbital Lesions in Saudi Arabia: A Multi-centered Demographic Study with Clinicopathological Correlation - Abrar K. Alsalamah; Azza MY. Maktabi; Hind M. Alkatan (Springer, 2020)
The demographics, clinical features, and histopathological classification of orbital space-occupying lesions in adults have not been widely described in our part of the world except for the pediatric population. In this retrospective study, we collected 110 consecutive adult patients (18 years and older) with orbital lesions (excluding lacrimal gland lesions) that were diagnosed histopathologically in two tertiary eye centers in Riyadh, Saudi Arabia (January 2000 to July 2017). Patients with thyroid-related orbitopathy, infectious, and inflammatory/pseudo-inflammatory lesions were excluded. We had 60 males (54.5%) and 50 females (45.5%). The mean age at presentation was 51.4 years (range 19-99). Proptosis was the most common clinical presentation (mean duration 15.4 months). The orbital lesions in order of increasing prevalence were: lymphoproliferative lesions in 26.4%; vascular in 21.8%; secondary tumors in 14.6%; neurogenic in 13.6%; structural in 10.0%; soft tissue tumors 8.2%; then metastatic tumors (2.7%) and others (extramedullary leukemia, fibrous dysplasia, and histiocytic lesion: Rosai-Dorfman disease): one case each. Gender distribution was varied in lymphoproliferative disorders compared to vascular lesions. Cavernous hemangioma was the most common vascular lesion (83.3%) and schwannoma was the most common neurogenic tumor (60%). Secondary lesions extended to the orbit mostly from eyelids in nine out of 16 or conjunctiva in four out of 16 cases. A favorable outcome was observed in about 80% of patients who underwent excisional biopsy. The rest encountered local recurrence of the tumors, growing of residual lesions, and recurrence with further invasion to nearby structures. We concluded having a similar demographic pattern of orbital lesions in adults as has been universally reported. We have fewer secondary tumors. We have summarized the pathological profile of adult orbital lesions according to patients' age, gender, symptoms, and location of the lesion as a baseline guide for proper diagnosis of any orbital mass prior to surgical management planning and for future prognostic studies.